Perceived Utilization of Leadership Styles Among Nurses - Gashaye M; Tilahun D; Belay A; Bereka B (Dove Medical Press, 2023)
Mihret Gashaye,1 Desalew Tilahun,2 Admasu Belay,2 Bayisa Bereka2 1Jimma Medical Center, Institute of Health, Jimma University, Jimma Town, Ethiopia; 2Nursing School, Faculty of Health Science, Institute of Health, Jimma University, Jimma Town, EthiopiaCorrespondence: Mihret Gashaye, Tel +251918314503 ; +251917557279, Email gamihret@gmail.comBackground: Nurses´ perceptions of leaders´ leadership styles has a significant impact on their well-being. Effective leadership in health care is crucial for improving and enhancing the effectiveness of health care systems. This study aimed to assess the perceived utilization of leadership styles among nurses at Jimma town public health facilities, Ethiopia.Methods: This facility-based cross-sectional study was conducted with 403 nurses. Data were collected through a self-administered structured questionnaire. Data were entered into Epi-Data version 4.6 and then exported to SPSS version 25. The strength of association was described using unstandardized adjusted β with a 95% confidence interval (CI) and p-value < 0.05.Results: Of the 422 participants, 403 completed and returned the questionnaire correctly, thus achieving a response rate of 95.5%. Staff nurses perceived that their head nurses fairly often or commonly used transformational leadership styles, with a mean of 2.77± 0.60. The multivariable linear regression analysis model indicated that there was a positive relationship between perceived leadership style and gender, overall organizational commitment, overall job-related stress, overall innovative work behavior, and overall leadership practice. However, there was a negative relationship between perceived leadership style and nurses who had not received previous training on leadership.Conclusion: This study highlights that transformational leadership is a commonly utilized leadership style by leader nurses. Effective and balanced use of various leadership styles requires knowledge (training), organizational commitment, and innovative work behavior from both leaders and staff nurses. Therefore, a transformational leadership style is key to achieving organizational goals and increasing staff nurses' productivity.Keywords: organizational commitment, job-related stress, innovative work behavior, leadership, leadership style, nurses, Jimma, Ethiopia